Sturge Weber Syndrome: A Case Report - Devkota, S; Upadhyay, S (Journal of Nepal Paediatric Society, 2010)
Sturge-Weber syndrome is a neurocutaneous syndrome characterized by port wine stain, congenital glaucoma, and underlying anomalous leptomeningeal venous plexus and the lack of normal cortical venous drainage. It is a congenital but not an inherited disease and it occurs sporadically and is very rare, incidence being approximately 1 on 50000. It occurs with rare exception but occasionally the other members of the family may have hemangiomata of a lesser degree. DOI: 10.3126/jnps.v30i3.3920 J Nep Paedtr Soc 2010;30(3):164-165